Single cell sequencing shines a light on malaria parasite relatedness in complex infections. Issue 2 (February 2020) - Siegel, Sasha V.; Rayner, Julian C.
Abstract : Recent genomic studies are investigating the wide-ranging implications of malaria complex infections on parasite diversity, transmission, and downstream disease eradication efforts. Using single cell sequencing, new work by Nkhoma et al. provides evidence that there is unexpectedly frequent co-transmission of related parasites in the intense transmission setting in Malawi.